The MSME's Loan Guarantee through KUR Program Implementation Create Fiscal Risk - Yasin, Akhmad (Badan kebijakan Fiskal, 2014)
This loan guarantee is awarded to viable MSMEs businesses (feasible) but they are not qualified to access credit/financing from banks (nonbankable). The implementation of the micro credit program involves three parties, namely the government, corporate underwriters, and banking. Results of this study is that the position of the government as the representative of the state in the context of business contracts included in the public legal action. Furthermore, public expenditure charged to the budget of income and expenditure (budget) in the form of state capital participation (PMN) and underwriting compensation (IJP) cause the transformation of the juridical laws from the state finances as public finance to privat finance of other legal entity. Fiscal risk would occur if the IJP increased funding requirements and the addition of PMN in guarantor state-owned enterprises (SOEs) are not sufficient so that resulting in the addition of a greater allocation of funds from the state budget. Under the provisions of the legislation of social welfare, fiscal risk status is a consequence of the law of state responsibility which has value, given the weighting of fiscal risk that promotes the interests and welfare of the community.